DETERMINATION OF THE BASIC SEMIOTIC UNITS IN THE FIELD OF DANCE - Zdravkova Djeparoska, Sonja (Alma Mater Press, 2020)
Semiotics as a science that studies signs, messages and codes is most often associated with linguistics and literature. The connection of the music and dance field with semiotics opens up opportunities for reading and decoding of the ascents that have not yet been or not sufficiently treated. General semiotic concepts will be applied in the field of dance, and their range, structure and function will be defined. Peterson Royce exposes the view that it is not possible to make a direct equalisation of the elements and its classifications that are functional in linguistics in comparison with performing arts concretely dance, due to a completely different concept and structure of the material. Hence, the attempt is to make classification, analysis and comparison of the generally accepted semiotic concepts with what is applicable in a dance performance. Theatrical / dramatic semiotics, which are significantly larger than the sources associated with dance semiotics will be considered. If we refer to the opinions of Mukařovsky regarding the definition of the basic element – the sign - and accept his classification of performance systems, we can get possible answers on this issue. The capacity and shape of a dance sign is determined and depends on the performance processes. The sign is encoded, recoded and interpreted. However, as a basic irreplaceable element of this analysis we use the dancing body, which is fundamental for modelling and coding.
Keywords: dance, semiotics, sign, dancing body